2006
DOI: 10.15288/jsa.2006.67.529
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous and Concurrent Polydrug Use of Alcohol and Prescription Drugs: Prevalence, Correlates, and Consequences

Abstract: ABSTRACT. Objective:In this study, we sought to examine the prevalence, correlates, and consequences associated with simultaneous polydrug use and concurrent polydrug use of alcohol and prescription drugs. For purposes of this investigation, simultaneous polydrug use referred to the co-ingestion of different drugs at the same time, and concurrent polydrug use referred to the use of different drugs on separate occasions within the past 12 months. Method: Undergraduate students attending a large public midwester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
208
2
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 269 publications
(245 citation statements)
references
References 35 publications
20
208
2
15
Order By: Relevance
“…Measures of more problematic or serious substance use-Although no standard definition, conceptualization, or measure currently exists for poly-substance use (Ives and Ghelani, 2006;Schensul et al, 2005), two common types of assessments include concurrent poly-substance use (i.e., more than one substance in a given time period) and simultaneous poly-substance use (i.e., the co-ingestion of different substances on the same occasion; see McCabe et al, 2006). Sneed et al (2004) examined three indices of lifetime polysubstance use: (a) an unweighted count of substances used; (b) a weighted substance use index where each substance was assigned a weight based upon severity (as determined by the researchers); and (c) a hierarchical index (i.e., ranging from alcohol or cigarettes, to use of both alcohol and cigarettes, to use of alcohol, cigarettes, and marijuana, to use of alcohol, cigarettes, marijuana plus one other illicit substance) and found basic functional equivalency among the three.…”
Section: 33mentioning
confidence: 99%
See 1 more Smart Citation
“…Measures of more problematic or serious substance use-Although no standard definition, conceptualization, or measure currently exists for poly-substance use (Ives and Ghelani, 2006;Schensul et al, 2005), two common types of assessments include concurrent poly-substance use (i.e., more than one substance in a given time period) and simultaneous poly-substance use (i.e., the co-ingestion of different substances on the same occasion; see McCabe et al, 2006). Sneed et al (2004) examined three indices of lifetime polysubstance use: (a) an unweighted count of substances used; (b) a weighted substance use index where each substance was assigned a weight based upon severity (as determined by the researchers); and (c) a hierarchical index (i.e., ranging from alcohol or cigarettes, to use of both alcohol and cigarettes, to use of alcohol, cigarettes, and marijuana, to use of alcohol, cigarettes, marijuana plus one other illicit substance) and found basic functional equivalency among the three.…”
Section: 33mentioning
confidence: 99%
“…Typically, as indicated by examination of patterns of use, individuals who initiate more than one substance progress from alcohol and/or tobacco as the first substance initiated to more "illicit" drugs, such as marijuana (Kandel and Yamaguchi, 2002). Further, research has consistently documented that a greater degree of substance involvement indicated by use of more than one substance leads to more problematic outcomes (Coffin et al, 2003;Degenhardt et al, 2007;Ives and Ghelani, 2006;McCabe et al, 2006;Schensul et al, 2005;Wish et al, 2006). For these reasons adolescents considered to be at higher risk were those who had initiated more than one substance.…”
Section: Pretest Equivalencementioning
confidence: 99%
“…La tendencia señalada se ha intensificado en los últimos decenios y ahora los estudiantes están inmersos en una cultura de abuso de sustancias adictivas que se traduce en una serie de efectos nocivos en el ámbito acadé-mico, la salud y en consecuencias sociales que se extienden a las comunidades circundantes. [4][5][6][7][8][9][10][11] Existen muy pocos datos disponibles sobre el uso indebido de drogas en estudiantes universitarios y estos se centran en el consumo de alcohol y los problemas relacionados en la universidad y estudiantes universitarios. Además, la mayoría de las investigaciones disponibles se concentran en la utilización de una única sustancia como el alcohol o la marihuana; con muy poca atención prestada al uso simultáneo de varias drogas.…”
Section: Introductionunclassified
“…The initial use of some drugs during adolescent period primes the brain to bolster consumption of illicit substances later in life, leading to polydrug use in some individuals (McCabe et al, 2006). For example, previous studies have shown that nicotine exposure during adolescence can pave the way to the use and abuse of cocaine, alcohol, and other addictive substances (Levine et al, 2011;McQuown et al, 2007;Orsini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%